2001
DOI: 10.1016/s0300-8932(01)76332-4
|View full text |Cite
|
Sign up to set email alerts
|

Variabilidad en el manejo hospitalario del infarto agudo de miocardio en España. Estudio IBERICA (Investigación, Búsqueda Específica y Registro de Isquemia Coronaria Aguda)

Abstract: Introduction and objective. Although some in-hospital studies have described the management of acute myocardial infarction (MI) patients in Spain, none has been able to guarantee the exhaustiveness of patient registry. This study sought to determine the clinical characteristics and in-hospital management of patients with MI in eight Spanish population registries.Methods. The IBERICA study is a population-based MI registry carried out in the 25 to 74 year-old population, in eight Spanish regions in 1997. A stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
19

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(29 citation statements)
references
References 34 publications
0
10
0
19
Order By: Relevance
“…En España se pueden obtener datos sobre la incidencia de la cardiopatía isquémica del programa MONICA-Cataluña (Sans et al, 2001), del registro REGICOR y del estudio IBERICA (Fiol et al, 2001). Estos estudios indican que la incidencia del IAM, al igual que ocurre con la mortalidad, es más baja que en otros países …”
Section: Epidemiología: Morbilidad Y Mortalidad Desagregada Por Sexosunclassified
“…En España se pueden obtener datos sobre la incidencia de la cardiopatía isquémica del programa MONICA-Cataluña (Sans et al, 2001), del registro REGICOR y del estudio IBERICA (Fiol et al, 2001). Estos estudios indican que la incidencia del IAM, al igual que ocurre con la mortalidad, es más baja que en otros países …”
Section: Epidemiología: Morbilidad Y Mortalidad Desagregada Por Sexosunclassified
“…El estudio IBERICA se diseñó para monitorizar y comparar las tasas de incidencia, ataque, mortalidad, y la letalidad a los 28 días del infarto agudo de miocardio (IAM), en distintas áreas de 8 comunidades autónomas: Castilla-La Mancha (Toledo y Albacete), Cataluña (Girona), Galicia (A Coruña), Islas Baleares (Mallorca), Valencia, Murcia, Navarra y País Vasco, entre los residentes de 25-74 años. Se utilizaron métodos similares en todas las áreas para detectar los casos y para registrar las características demográficas, clínicas y las complicaciones, incluyendo las muertes en los primeros 28 días tras el inicio de los síntomas 13,14 . Para la detección de los casos de IAM hospitalizados se realizó una búsqueda activa en todos los hospitales, públicos y privados, utilizando como fuentes de información las unidades de cuidados intensivos cardiológicos, servicios de cardiología y listados de altas hospitalarias.…”
Section: Materials Y Métodosunclassified
“…Currently, in Spain, the prevalence of smoking is 35.4% in patients with acute myocardial infarction and about 32% in patients with angina pectoris. Overall, it is estimated that 29% of deaths from coronary heart disease are due to smoking, and 1 in 3 deaths caused by smoking is premature [13,14]. Therefore, smoking increases cardiovascular risk in both diabetics and nondiabetics [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows that smoking cessation leads to reduced cardiovascular risk [15,16,19]. Studies have shown a reduction in the incidence of CVEs and a decrease in symptoms of arteriosclerotic disease in patients with heart disease who stop smoking [13,15,20]. There is abundant evidence that smoking in diabetic patients is associated with a worse prognosis and acceleration of vascular complications and that cessation provides early benefits [20,21].…”
Section: Introductionmentioning
confidence: 99%